Indigenously produced biochar retains fertility in sandy soil through unique microbial diversity sustenance: a step toward the circular economy - Khan, Munawwar Ali; Salman, Alsayeda Zahra; Khan, Shams Tabrez (Frontiers in Microbiology, 2023)
Agricultural productivity in the arid hot desert climate of UAE is limited by the unavailability of water, high temperature, and salt stresses. Growing enough food under abiotic stresses, and decreasing reliance on imports in an era of global warming is a challenge. Biochar with high water and nutrient retention capacity and acid neutralization activity is an attractive soil conditioner. This study investigates the microbial community in the arid soil of Dubai under shade house conditions irrigated with saline water and the shift in the microbial community following long-term amendment with Biochar indigenously prepared from date palm waste. Illumina sequencing was used to elucidate changes in bacterial, archaeal, and fungal community structures in response to long-term biochar amendment. Samples were collected from quinoa fields receiving standard NPK doses and from fields receiving 20 and 30 tonnes ha-1 of biochar in addition to NPK for one year. Water holding capacity, pH, electrical conductivity, calcium, magnesium, chloride, potassium, sodium, phosphorus, and total nitrogen in the soil from biochar-treated and untreated controls were determined. The results show that soil amendment with biochar helps retain archaeal and bacterial diversity. Analysis of differentially abundant bacterial and fungal genera indicates enrichment of plant growth-promoting microorganisms. Interestingly, many of the abundant genera are known to tolerate salt stress and some observed genera were of marine origin. Various physicochemical properties of soil receiving 30 tonnes ha-1 of biochar improved significantly over the control soil. This study strongly suggests that biochar helps retain soil fertility by enriching plant growth-promoting microorganisms.